Association of Trauma Type, Age of Exposure, and Frequency in Childhood and Adolescence With Psychotic Experiences in Early Adulthood - Croft, Jazz (JAMA Psychiatry, 2018)
IMPORTANCE: Cross-sectional and longitudinal studies have consistently reported associations between childhood trauma and psychotic experiences and disorders. However, few studies have examined whether the age of exposure or specific trauma types are differently associated with the risk of developing psychotic experiences. OBJECTIVE: To examine whether exposure to trauma, assessed at multiple age periods between 0 and 17 years of age, is associated with an increased risk of psychotic experiences by age 18 years and whether this association varies according to trauma type as well as age and frequency of exposure. DESIGN, SETTING, AND PARTICIPANTS: This study used data from the Avon Longitudinal Study of Parents and Children, a large population-based birth cohort in the United Kingdom that recruited women who resided in the Avon Health Authority area and had an expected delivery date between April 1, 1991, and December 31, 1992. Data on psychotic experiences were included in the study, along with trauma variables derived from assessments completed by the parents or self-reported by the participants. The variables represent exposure to any trauma type between ages 0 and 17 years; any trauma type within a distinct age period: early childhood (0-4.9 years), middle childhood (5-10.9 years), or adolescence (11-17 years); specific trauma types between ages 0 and 17 years; and specific trauma types within early childhood, middle childhood, or adolescence. Data were analyzed from January 9, 2017, to November 30, 2017. MAIN OUTCOMES AND MEASURES: Suspected or definite psychotic experiences were assessed using the psychosis-like symptoms semistructured interview at age 12 years and then at age 18 years. RESULTS: The sample of 4433 participants included 2504 (56.5%) females, with a mean (SD) age of 17.8 (0.38) years. Exposure to any trauma up to age 17 years was associated with increased odds of psychotic experiences at age 18 years (adjusted odds ratio, 2.91; 95% CI, 2.15-3.93). All trauma types from age 0 to 17 years were associated with an increased odds of psychotic experiences. The population-attributable fraction for childhood and adolescent trauma on psychotic experiences at age 18 years was 45% (95% CI, 25%-60%). Effect sizes for most trauma types were greater for exposure that was more proximal to the outcome, although CIs overlapped with those for more distal trauma. Evidence supported dose-response associations for exposure to multiple trauma types and at multiple age periods. In an analysis aimed at minimizing reverse causality, adolescent trauma was also associated with past-year incident psychotic experiences at age 18 years. CONCLUSIONS AND RELEVANCE: These findings are consistent with the thesis that trauma could have a causal association with psychotic experiences; if so, identification of modifiable mediators is required to inform prevention strategies.